2018
DOI: 10.4172/2161-1068.1000257
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcomes among Patients Treated With Category II Antituberculosis Regimen: Short Review

Abstract: Tuberculosis (TB) is one of the leading causes of morbidity and mortality, especially in developing and underdeveloped nations. To add to the burden, drug resistant TB is on the rise and India is handling the dual burden of drug sensitive TB and resistant TB. Previously treated TB cases when compared to the newly diagnosed, have poor treatment success rates and nearly seven times higher incidence of multi drug resistant TB. Proper management of patients treated with Category-II anti-tuberculous treatment (ATT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…A couple of studies done outside India have not shown any statistically significant difference between the treatment outcomes and medication policies of daily medication and thrice-weekly medication as described by the program. [ 6 , 7 ] The current NTEP guidelines suggest daily FDC to all diagnosed TB patients irrespective of the category of treatment. The present study was conducted to assess sociodemographic and clinical characteristics and the treatment outcomes of patients on FDC daily regimen.…”
Section: Introductionmentioning
confidence: 99%
“…A couple of studies done outside India have not shown any statistically significant difference between the treatment outcomes and medication policies of daily medication and thrice-weekly medication as described by the program. [ 6 , 7 ] The current NTEP guidelines suggest daily FDC to all diagnosed TB patients irrespective of the category of treatment. The present study was conducted to assess sociodemographic and clinical characteristics and the treatment outcomes of patients on FDC daily regimen.…”
Section: Introductionmentioning
confidence: 99%